Efficacy of Molecular Identification Using DNA Barcoding Technique of Freshwater Edible Molluscs from Nagaland, India - Imsong, Lanusangla; Murali , M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Freshwater molluscs are widely utilized for food and medicine in many regions of the world. One such area in India is the northeast, where tribal and economically underdeveloped communities consume freshwater molluscs. Because they are an inexpensive source of protein and offer food security, livelihoods, and medicine, these molluscs are in great demand. In the present work, molecular identification and documentation of the edible gastropods of Nagaland is done. Throughout the twentieth century, identification was based on morphology and anatomy. However, the identification based on morphological structure is challenging due to the existence of cryptic species that shows similar morphology which can lead to erroneous identification of species. Freshwater molluscs shells are highly varied and exhibit convergence evolution and hence may not always accurately indicate systematic boundaries. Thus, DNA bar-coding is a potential method for taxonomic identification process that can mitigate this problem. It uses genetic markers such as cytochrome oxidase I (COI) gene, 16S rDNA and 18S rDNA. In the present study COI mitochondrial gene is used. A fragment of COI gene is sequenced and their DNA is compared to the existing sequences in the genomic library. The sequence is then submitted in NCBI to obtain accession number. A total of 7 species of edible freshwater molluscs belonging to two class bivalvia and gastropoda was collected from local fishery ponds, confined water bodies, rivers, streams, and were identified. The identified species with their accession number is as follows, Lamellidens marginalis (ON209524), Parreysia corrugata (OM074301), Indonaia subclatharata (OM075118), Indonaia caerulea (OM076974), Bellamaya bengalensis (OM056888), Paludomus sp (OM078498), Brotia costula (OM056887). The study provides substantial support for COI's effectiveness as a prime marker for DNA barcoding of Indian edible freshwater gastropods and bivalves.